A city scale degree-day method to assess building space heating energy demands in Strasbourg Eurometropolis (France). (15th December 2016) - Kohler, M.; Blond, N.; Clappier, A.
Highlights: Energy profiles are numerically modeled at city scale. They integrate the urban heat island complexity and building internal heat gains. Based on degree-days a fast energy management tool for urban planner is then framed. Reliable estimates of urban-scale building energy loads are obtained. Degree-day daily temperature definition causes the largest results' discrepancies. Abstract: Efficient strategies are required to reduce space heating energy demands in buildings at city scale. Models taking into account the dynamic of the Urban Heat Island (UHI) phenomenon may be useful tools to help urban planners in this task. In this paper, we propose a new methodology to assess the energy demands for space heating in buildings at city scale: a degree-day method is applied, coupled with the use of a dynamic urban meteorological model that computes a building energy budget. First, it is shown that the total building space heating energy demand at city scale, as simulated by the meteorological model, is quasi- linearly dependent on the daily mean city scale air temperature. The developed city-scale degree-day method applied to assess the space heating energy demands in Strasbourg Eurometropolis (France) is shown to be consistent with the estimates issued by local official energy sources. A sensitivity analysis highlights the fact that while the heating energy demands are dependent on the building insulation performance and thermostat heating temperatures, scenarios in which building energy properties are changed do not significantly affect the UHI.